2014
DOI: 10.1007/s10924-014-0684-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Recycling of Poly(3-Hydroxybutyrate-co-3-Hydroxyvalerate)/Polylactide Based Blends

Abstract: The effects of recycling cycles (up to six repeated cycles) on the structure and properties of neat poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), neat polylactide (PLA) and PHBV/PLA: 50/50 (wt%) blends elaborated by melt molding process were investigated. The changes in the chemical structure, the morphology and the thermal, mechanical and rheological properties of the recycled materials were studied. The reduction of molecular weights of both PHBV and PLA showed the predominance of chain scission mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Both types of molecular weights, weight averaged ( ) and number averaged ( ), showed a decrease with successive recycling. These results agree with the work of other researchers [25]. The polydispersity index (PDI) showed an increase with increased number of reprocessing cycles.…”
Section: Effect Of Recycling On Fibersupporting
confidence: 93%
“…Both types of molecular weights, weight averaged ( ) and number averaged ( ), showed a decrease with successive recycling. These results agree with the work of other researchers [25]. The polydispersity index (PDI) showed an increase with increased number of reprocessing cycles.…”
Section: Effect Of Recycling On Fibersupporting
confidence: 93%
“…Traditional simulation of mechanical recycling by multiple processing and servicelife by accelerated thermal ageing was previously developed for commodities such as PE [264], PP [265], poly(styrene) (PS) [191], [192], poly(vinyl chloride) (PVC) [266] or PET [179], [267]- [269], among others. Concerning bio-based polymers, the main effort has been dedicated to PLA in great extension, and other materials such as PHAs [270]- [272], poly(caprolactone) [273] or biocomposites with matrixes of PLA or thermoplastic starch (TPS) [274].…”
Section: Materials Valorisation Of Biopolymersmentioning
confidence: 99%
“…Studies focused on the characterization of multi-injected PCL have revealed that PCL technological waste is suitable to be reused as an additive to a neat polymer [273]. Regarding PHAs, their performance of mechanical recycling was tested during successive injection [270], [271] and extrusion cycles [272], showing successive diminution of molecular weight after increasing cycles, with its consequent decrease in mechanical properties. within the same polymer fraction, or in combination with other material, which hinders the continuation of material flow inside the mechanical recycling loop and thus suggests the design for further valorization.…”
Section: Materials Valorisation Of Biopolymersmentioning
confidence: 99%
“…Wu et al [31] reported an improvement in the miscibility between PLA and PCL when multiwalled carbon nanotubes were added, which was attributed to the emulsification that occurred at the interface in the presence of the amphiphilic carboxylic MWCNTs, leading to a thermodynamic stabilization of the interface. PLA/PHBV blends and their blend nanocomposites were also studied, but to a lesser extend [2,[38][39][40][41]. Ma et al [2] reported that the storage modulus of PLA was higher than that of PHBV in the glassy state, and blending of the polymers and an increase in the PHBV content reduced the storage modulus of PLA.…”
Section: Introductionmentioning
confidence: 99%